2022
DOI: 10.1039/d1sm01204e
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of the size of a droplet emerging from a pore opening into a crossflow field

Abstract: The problem of termination of a droplet at the surface of a membrane in crossflow field is an important topic in the context of controlled emulsification of fluids. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The idea behind the PFPT is to mitigate fouling by preventing the accumulation of oil droplets at the membrane surface during filtration. The fate of an oil droplet during filtration has been comprehensively studied using computational fluid dynamics (CFD) [29][30][31][32][33][34][35] and direct observation over the membrane surface [36] to understand the physics behind the oil settling and clogging of membrane pores. The results showed that an oil droplet, during the filtration process, undergoes either of the following four fates, namely 1) rejection, 2) permeation, 3) pinning, or 4) breakup.…”
Section: Periodic Feed Pressure Techniquementioning
confidence: 99%
“…The idea behind the PFPT is to mitigate fouling by preventing the accumulation of oil droplets at the membrane surface during filtration. The fate of an oil droplet during filtration has been comprehensively studied using computational fluid dynamics (CFD) [29][30][31][32][33][34][35] and direct observation over the membrane surface [36] to understand the physics behind the oil settling and clogging of membrane pores. The results showed that an oil droplet, during the filtration process, undergoes either of the following four fates, namely 1) rejection, 2) permeation, 3) pinning, or 4) breakup.…”
Section: Periodic Feed Pressure Techniquementioning
confidence: 99%
“…Dimensionless numbers are used to provide criteria on the significance of each of the forces and the patterns of the flow. For example, the significance of interfacial tension force in relation to viscous force is measured via the capillary number ( Ca ). Ca is defined as, Ca = μV/γ , where μ is the dynamic viscosity, V is a characteristic velocity, and γ is the interfacial tension. The Bond number ( Bo ), on the other hand, measures the relative importance of gravitational force compared to interfacial tension force and is used to characterize the shape of bubbles or drops moving in a surrounding fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The Bond number ( Bo ), on the other hand, measures the relative importance of gravitational force compared to interfacial tension force and is used to characterize the shape of bubbles or drops moving in a surrounding fluid. Bo is defined as, Bo = Δ ρgL 2 /γ, where Δρ is the density difference between the continuous and the dispersed phases, g is the gravity, L is some characteristic length scale, and γ is the interfacial tension. , Likewise, Weber number ( We ) measures the ratio between inertial and interfacial tension forces and takes the form We = ρVL/γ . These numbers provide criteria on when capillary forces may be important and when it may be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement of one fluid by another immiscible one is a phenomenon of great importance and finds direct application in many processes. Examples of these processes include petroleum production, filtration/separation operations, pharmaceutical and food industries, and many others. Between any two immiscible fluids in contact, there exists an interface that separates one fluid from the other. Such an interface represents a surface of discontinuity that is generally curvilinear.…”
Section: Introductionmentioning
confidence: 99%
“…There are other applications in which emerging droplets are forced to terminate earlier by the action of some external forces (e.g., hydrodynamic drag). This finds applications in pharmaceutical industries where the production of nearly uniform-sized emulsions is desirable to achieve uniform release profiles of the drugs . While the breakup phenomenon of an emerging or permeating droplet by a crossflow field has been studied extensively in the context of oily water filtration, the topic is fundamentally so rich to warrant further investigation. The framework, which has been adapted to define the critical conditions for breakup of permeating/emerging droplets, has been based on constructing a torque balance of the involved forces around a pivotal point …”
Section: Introductionmentioning
confidence: 99%